Arterial Stiffness, Subendocardial Impairment, and 30-Day Readmission in Heart Failure Older Patients - Fantin, Francesco; Giani, Anna; Franconi, Arianna; Zoico, Elena; Urbani, Silvia; Rossi, Andrea P.; Mazzali, Gloria; Zamboni, Mauro (Frontiers in Cardiovascular Medicine, 2022)
Arterial stiffness and subendocardial perfusion impairment may play a significant role in heart failure outcome. Aim of the study was to examine the main predictors of 30-days readmission in geriatric patients, hospitalized with heart failure, exploring hemodynamical parameters, arterial stiffness indexes and subendocardial viability ratio (SEVR). 41 hospitalized patients, affected by heart failure, were included; they underwent clinical evaluation, routine laboratory testing, and echocardiography. At admission time, after achievement of clinical stability (defined as switching from intravenous to oral diuretic therapy) and at discharge, arterial tonometry was performed to evaluate carotid-femoral pulse wave velocity -PWVcf- and SEVR (then corrected for hemoglobin concentration and oxygen saturation). Through the evaluations, a significant progressive decrease in PWVcf was described (17.79±4.49 m/s, 13.54±4.54 m/s, 9.94±3.73 m/s), even after adjustment for age, gender, mean arterial pressure (MAP) variation and left ventricular ejection fraction (LVEF). A significant improvement was registered for both SEVR (83.48±24.43, 97.94±26.84, 113.29±38.02) and corrected SEVR (12.74±4.69, 15.71±5.30, 18.55±6.66) values, and it was still significant when adjusted for age, gender, MAP variation and LVEF. After discharge, 26.8% of patients was readmitted within 30 days. In a multivariate binary logistic regression analysis, PWVcf at discharge was the only predictor of 30 days readmission (OR 1,957, 1,112-3,443) In conclusion, medical therapy seems to improve arterial stiffness and subendocardial perfusion in geriatric patients hospitalized with hearth failure. Furthermore, PWVcf is a valid predictor of 30-days readmission. Its feasibility in clinical practice may provide an instrument to detect heart failure patients at high risk of rehospitalization.